2017
DOI: 10.1016/j.phrs.2017.02.023
|View full text |Cite
|
Sign up to set email alerts
|

Emerging therapeutic targets in cancer induced bone disease: A focus on the peripheral type 2 cannabinoid receptor

Abstract: Skeletal complications are a common cause of morbidity in patients with primary bone cancer and bone metastases. The type 2 cannabinoid (Cnr2) receptor is implicated in cancer, bone metabolism and pain perception. Emerging data have uncovered the role of Cnr2 in the regulation of tumour-bone cell interactions and suggest that agents that target Cnr2 in the skeleton have potential efficacy in the reduction of skeletal complications associated with cancer. This review aims to provide an overview of findings rela… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
21
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
2
1

Relationship

2
8

Authors

Journals

citations
Cited by 33 publications
(24 citation statements)
references
References 180 publications
(229 reference statements)
3
21
0
Order By: Relevance
“…Patients with primary bone cancer, like OS, and bone metastases commonly acquire cancer-induced bone disease (CIBD), presenting several troubles such as bone pain, restricted mobility, high rate of fractures, nerve compression, and hypercalcemia. It has been observed that pharmacological and genetic manipulation of CB2 reduces the progression of CIBD [107]. In particular, its activation with specific ligands acts directly on tumor-inducing apoptosis or necrosis in malignant cells, but also on osteoclasts, inhibiting their formation and differentiation.…”
Section: Endocannabinoid/endovanilloid System In Bone Cancermentioning
confidence: 99%
“…Patients with primary bone cancer, like OS, and bone metastases commonly acquire cancer-induced bone disease (CIBD), presenting several troubles such as bone pain, restricted mobility, high rate of fractures, nerve compression, and hypercalcemia. It has been observed that pharmacological and genetic manipulation of CB2 reduces the progression of CIBD [107]. In particular, its activation with specific ligands acts directly on tumor-inducing apoptosis or necrosis in malignant cells, but also on osteoclasts, inhibiting their formation and differentiation.…”
Section: Endocannabinoid/endovanilloid System In Bone Cancermentioning
confidence: 99%
“…Another report has depicted that CBR deficiency could restrain loss of bone [32,36]. Growing data have disclosed that targetting CB 2 R in the bone possesses potential efficacy in the reduction in bone syndrome related to cancer [33]. In spite of this, there are no data available to date concerning the function of MDA19 on OS.…”
Section: Discussionmentioning
confidence: 99%
“…and AM630 have more specific actions on effector cells and tissues by targeting CB2 receptors (Marino & Idris, 2017).…”
Section: Synthetic Cannabinoidsmentioning
confidence: 99%